2007
DOI: 10.1111/j.1532-5415.2007.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Caregiver Burden from Daily Functional Abilities of Patients with Mild Dementia

Abstract: OBJECTIVES-To assess the relationship between performance-and informant-based measures of activities of daily living (ADLs) in patients with early dementia and burden or psychological distress experienced by the patients' caregivers. DESIGN-Descriptive study. SETTING-Ambulatory center.PARTICIPANTS-Thirty-four patient-caregiver dyads in which the patient had mild dementia (Mini-Mental State Examination score ≥ 17).MEASUREMENTS-A performance-based ADL measure (the Direct Assessment of Functional Status (DAFS)) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 26 publications
(29 reference statements)
12
124
3
7
Order By: Relevance
“…This result corroborates previous research [14,43,44] reporting that a cognitive decline usually appears early in the course of de- mentia and is followed by disturbances in ADL and IADL functioning, which increase caregiver burden. This result concurs with the study of Razani et al [45] , who reported that the ADL/IADL abilities of dementia patients can predict caregiver burden. Some cross-cultural research reports [46,47] have stated that the Confucian attitude of respecting elders could reduce caregiver burden, but within a Korean framework (in which almost all caregivers are a spouse or a son and daughter-in-law pair), a decline in ADL/IADL function is likely to produce a large burden.…”
Section: Discussionsupporting
confidence: 80%
“…This result corroborates previous research [14,43,44] reporting that a cognitive decline usually appears early in the course of de- mentia and is followed by disturbances in ADL and IADL functioning, which increase caregiver burden. This result concurs with the study of Razani et al [45] , who reported that the ADL/IADL abilities of dementia patients can predict caregiver burden. Some cross-cultural research reports [46,47] have stated that the Confucian attitude of respecting elders could reduce caregiver burden, but within a Korean framework (in which almost all caregivers are a spouse or a son and daughter-in-law pair), a decline in ADL/IADL function is likely to produce a large burden.…”
Section: Discussionsupporting
confidence: 80%
“…Activities of daily living refer to functional issues such as personal hygiene or the participation in leisure activities [27]. Consistently, a recent study has shown that high transdermal rivastigmine doses help to preserve patients’ functional integrity without compromising safety or tolerability [31], an aspect that poses a considerable impact on caregiver burden [32]. Notwithstanding, greater satisfaction was also related to the impact of undesirable side effects and the subjective effectiveness of treatment.…”
Section: Resultsmentioning
confidence: 82%
“…Regarding a neuropsychiatric profile's impact on caregiver burden, we detected an association between behavioral disturbances and caregiver burden in each cluster of patients [4,16,[18][19][20][21] . In the psychotic/behavioral cluster, the caregiver burden seemed to be affected by the overall behavioral symptomatology, and we did not identify a prevalent symptom related to caregiver burden.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the link between BPSD and negative outcomes in caregivers has been well documented; caregivers of patients with dementia report physical and emotional distress, and the presence of BPSD seems to be related with reductions in both patient's and caregiver's quality of life [4,[16][17][18][19][20][21] .…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%